Ten questions concerning dynamic sensory variation in salutogenic building design - Rossano Albatici; Yuri Bozzi; Massimo Pizzato; Simone Torresin; Luca Zaniboni (Building and Environment, 2026)

Smells modulate thermal sensation: A multisensory study in office environments during winter - Giulia Torriani; Simone Torresin; Francesco Babich; Massimiliano Zampini; Rossano Albatici (Building and Environment, 2026)

Corrigendum to “Combined and cross-modal effects of acoustic and indoor air quality conditions on sensory and cognitive responses of university students” [Building and Environment 288 (2026) 114005] - Matteo Pellegatti; Chiara Visentin; Simone Torresin; Francesco Babich; Pawel Wargocki; Nicola Prodi (Building and Environment, 2026)

Combined and cross-modal effects of acoustic and indoor air quality conditions on sensory and cognitive responses of university students - Matteo Pellegatti; Chiara Visentin; Simone Torresin; Francesco Babich; Pawel Wargocki; Nicola Prodi (Building and Environment, 2026)

Definition and performance of acoustic personalised environmental control systems (acoustic PECS): A systematic review - Simone Torresin; Larissa Pereira de Souza; Seda Yuksel Dicle; Douaa Al-Assaad; Francesco Aletta; Alvaro Balderrama; Mariya P. Bivolarova; Pyoung-Jik Lee; Josep Llorca-Bofí; Henna Maula; Alessandra Luna Navarro; Ilaria Pigliautile; et al. (Building and Environment, 2025)

Developing a principal components model of indoor smellscape perception in office buildings - Giulia Torriani; Rossano Albatici; Francesco Babich; Massimo Vescovi; Massimiliano Zampini; Simone Torresin (Building and Environment, 2025)

Thermal comfort and perceived air quality (PAQ) using automatic ceiling fans in residential buildings - Akshit Gupta; Giulia Torriani; Simone Torresin; Lorenza Pistore; Matteo Pellegatti; Lucia Piazza; Fabrizio Miorin; Wilmer Pasut; Annamaria Belleri; Roberto Lollini; Francesco Babich (Energy and Buildings, 2025)

Ten questions concerning Architectural Acoustics - Louena Shtrepi; Francesco Aletta; Lukas Aspöck; Arianna Astolfi; Janina Fels; Maarten Hornikx; Kristian Jambrošić; Cheol-Ho Jeong; Eckhard Kahle; Josep Llorca-Bofí; Jens Holger Rindel; Monika Rychtáriková; et al. (Building and Environment, 2024)

Factors influencing window opening behavior and mechanical ventilation usage during summertime: A case study in UK dwellings - Simone Torresin; Francesco Aletta; Tin Oberman; Rossano Albatici; Jian Kang (Building and Environment, 2024)

Perceived air quality (PAQ) assessment methods in office buildings: A systematic review towards an indoor smellscape approach - Giulia Torriani; Simone Torresin; Irene Lara-Ibeas; Rossano Albatici; Francesco Babich (Building and Environment, 2024)

Effects of Biophilic Design interventions on university students' cognitive performance: An audio-visual experimental study in an Immersive Virtual office Environment - Arianna Latini; Simone Torresin; Tin Oberman; Elisa Di Giuseppe; Francesco Aletta; Jian Kang; Marco D'Orazio (Building and Environment, 2024)

Adoption of ISO/TS 12913-2:2018 Protocols for Data Collection From Individuals in Soundscape Studies: an Overview of the Literature - Francesco Aletta; Simone Torresin (Current Pollution Reports, 2023)
Purpose of Review The article reviews the literature on soundscape studies to analyse (i) which of the methods included in the Technical Specification (TS) 12913-2:2018 by the International Organization for Standardization (ISO) for collecting soundscape data from individuals are predominantly used in scientific research and (ii) what is the level of compliance with ISO recommendations of the methods employed in scientific research. Recent Findings The ISO/TS 12913-2:2018 provide three possible protocols for individuals’ soundscape data collection (Methods A, B, and C). Despite standardization efforts, a reference method has yet to be identified to improve comparability amongst studies and the formation of scientific evidence. Summary The analysis of 50 peer-reviewed papers published from 2018 (year of release of ISO/TS 12913-2) showed that Method A is the prevalent one, adopted by 94.4% of the identified studies. Full compliance with ISO technical specification recommendations is in any case quite limited, and almost no study is strictly adhering to them. Attributes are not always suitable to cover all the acoustic contexts (e.g. indoor environments). This is an indicator that the field is still developing, but it also signals that technical specification recommendations leave room for ambiguity or are not always implementable. This study is ultimately intended to offer recommendations on future development of the protocols in the standardization process. Graphical Abstract

Measuring, representing and analysing indoor soundscapes: A data collection campaign in residential buildings with natural and mechanical ventilation in England - Simone Torresin; Francesco Aletta; Tin Oberman; Veronica Vinciotti; Rossano Albatici; Jian Kang (Building and Environment, 2023)

Indoor soundscape, speech perception, and cognition in classrooms: A systematic review on the effects of ventilation-related sounds on students - Matteo Pellegatti; Simone Torresin; Chiara Visentin; Francesco Babich; Nicola Prodi (Building and Environment, 2023)

Supportive soundscapes are crucial for sustainable environments - Jian Kang; Francesco Aletta; Tin Oberman; Andrew Mitchell; Mercede Erfanian; Huan Tong; Simone Torresin; Chunyang Xu; Tingting Yang; Xiaochao Chen (Science of The Total Environment, 2023)